Financing Credit Home Ownership Through Contract Murabahah in Sharia Financial Institutions - Ingka, hasanuddin; Ridwan, Muhammad; Mustamin, Siti Walidah; Mustika, Mega (ASAS, 2024)
This research aims to analyze home ownership credit (KPR) financing through murabahah contracts at sharia financial institutions. Murabahah contracts are one of the popular financing instruments in sharia banking because of their transparent and fair principles, and in accordance with Islamic sharia which avoids usury and gharar. Through qualitative descriptive methods, this research identifies the operational mechanisms of murabahah contracts in mortgage financing, examines the benefits offered, and evaluates the challenges faced by sharia financial institutions in their implementation. The research results show that murabahah contracts provide various benefits for customers, such as price certainty and fixed installments, which makes financial planning easier. In addition, transparency in the transaction process increases customer trust in Islamic financial institutions. However, this research also found several challenges, including quite high credit risk, the need for a better understanding of sharia products among the public, and compliance with strict regulations.Keywords: KPR financing; Murabahah Agreement; Sharia Financial Institutions; Credit Risk; Community Education